CHEMISTRY MOBILE LEARNING DALAM PENINGKATAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK - Meydia Afrina (Direktorat Guru Pendidikan Menengah dan Pendidikan Khusus, 2022)
The subject matter of benzene taught in grade XII is a subject matter that is very closely related to phenomena in everyday life. Therefore, it needs a medium that is able to convey information appropriately, clearly and pleasantly so that the concept of the material is conveyed to the learner so that the learner understands the benzene material. Chemistry Mobile Learning is an android-based media that uses smart apps creator software. In this media there are several features, namely competencies, materials, evaluations, author, reference and about application that can be accessed with android. This study aims to find out the characteristics of chemistry mobile learning developed, to know the influence of chemistry mobile learning on the activeness of learners in benzene learning, and to know the effectiveness of chemistry mobile learning media to improve students' critical thinking ability in chemistry. This type of research is research development with the model of analysis, design, development, implementation, evaluation (ADDIE). Data is collected with response questionnaires, validation questionnaires, pretests and posttests. Data is analyzed with eligible percentages, qualified categorization, and N-gain tests. Response practitioners and students are highly qualified with 80.95% and 89.50% respectively. Effectiveness trial obtained 0.72 N-gain with high category. It can be concluded that chemistry mobile learning is effective to improve critical thinking ability in benzene material.